The olivocochlear system and protection from acoustic trauma: a mini literature review - Fuente, Adrian (Frontiers in Systems Neuroscience, 2015)
Large intersubject variability in the susceptibility to noise-induced hearing loss (NIHL) is known to occur in both humans and animals. It has been suggested that the olivocochlear system (OCS) plays a significant role in protecting the cochlea from exposure to high levels of noise. A mini literature review about the scientific evidence from animal and human studies about the association between the function of the OCS and susceptibility to NIHL was carried out. Animal data consistently show that de-efferented ears exhibit larger temporary threshold shift (TTS) and permanent threshold shift than efferented ears. Data from human studies do not consistently show a correlation between the strength of the OCS function and amount of TTS. Further research on human subjects is required to determine how the OCS function could be used to predict susceptibility to NIHL in individual subjects.